Understanding the strategies used for identification and provisions made available for Specific Learning Difficulties (Dyslexia) in the primary sections of two private mainstream schools in Dubai: An exploratory study. - Shaikh, Misbah (2020)
Striving to bridge the gap of education inequity serves as the main driving purpose for my research. Eventually being able to factor systemic change at the grassroot level with the aim to contribute to policy development and objectively upholding and promotion of successful inclusion in regular classrooms. The primary purpose of the research design in this dissertation was to investigate and understand the strategies used for identification and provisions made available for Specific Learning Difficulties (Dyslexia) in the primary sections of two private mainstream schools in Dubai. As a constructivist researcher I used the qualitative research approach for coding and analysing, gathering data from the emerging themes through triangulation and multiple case study design backed up with Frith’s causal model. This helped the researcher in shedding light on factors used as understudy to get a comprehensive understanding on the identification, intervention, strategies and teacher trainings etc. The research findings suggested that although historically UAE has been a champion of the cause, there is always room for improvement in the diagnosis, intervention, pastoral care and emotional support being offered to the learners with SpLD (dyslexia). Involvement of all stakeholders in school, parent training and support to be offered for better childcare as a reassurance that dyslexia can be managed and doesn’t have to be treated as a disability. Lastly, the research concluded with recommendations for the future.